Peran Kesetaraan Gender dalam Meningkatkan Produktivitas SDM dan Pertumbuhan Ekonomi - Sriharini, Sriharini; Al Fajar, Adam Hafidz; Syamraeni, Syamraeni; Mudfainna, Mudfainna; Sari, Novinta (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2024)
This study aims to explore how gender equality can enhance human resource (HR) productivity and support inclusive economic growth. Using a qualitative method based on literature review, this research analyzes relevant academic literature to identify the relationship between gender equality, HR productivity, and economic growth. The findings reveal that gender equality plays a significant role in improving HR productivity by fostering more innovative and collaborative work teams. Increased access for women to education and training leads to substantial contributions in formal sectors, which in turn supports economic diversification and innovation. However, the study also highlights challenges in implementing gender equality, such as structural injustice, gender stereotypes, and insufficient support for women balancing dual roles as workers and caregivers. As recommendations, governments and companies should adopt gender-responsive policies, including equal pay, flexible work arrangements, and childcare facilities. Additionally, public awareness campaigns are needed to shift social norms that restrict women's roles. With strategic measures, gender equality can significantly contribute to sustainable economic development.